Functional identification of a Ligase in the Red Sea Atlantis II deepest Layer - Mohammed, Mahera (AUC Knowledge Fountain, 2014)
Red sea, described as one of the unique marine ecosystems, incorporates up to 25 deep-sea brine pools. These pools posses multiple extreme conditions influencing the evolution and survival of their inhabiting microbial community. The combination of maximum depth (2194 m), high temperature (68C), anoxia, high salinity (26%), high pressure and high concentrations of heavy metals in the lower convective layer (LCL) of the Atlantis II brine pool makes it an ideal environment for identification of novel enzymes with unique characteristics and potential biotechnological applications. Here we describe the identification and the preliminary in vivo functional investigation of the ligase domain of an ATP-dependent DNA ligase from the DNA of the prokaryotic community extracted from water samples of the LCL of Atlantis II brine pool. Previously, these water samples were serially filtered on different membranes and the DNA isolated from the 0.1m filter was subjected to 454 pyrosequencing. A metagenomic dataset was initiated and used in this study to mine for genes encoding DNA ligases through Pfam search of conserved domains. The search and subsequent bioinformatic analysis resulted in the identification of a contig harboring an ORF of 915 bp (305 amino acids) that encodes a putative DNA ligase (LigATII). Homology search of the putative DNA ligase showed highest similarity to Erysiopelotrichaceae Bacterium (39% identity, 54% positive). LigATII displays modular architecture that is similar to two distinct domains-(the adenylation domain of LigD and the oligonucleotide binding (OB) fold domain)-that are conserved in ATP-dependent DNA ligases. Functional annotation of the LigATII ORF, identification of the functional conserved amino acids by the Consurf tool, 3D modeling and comprehensive phylogenetic analysis were conducted. These analyses have revealed the relatedness of LigATII to the family of ATP-dependent DNA ligases that has been recently identified through computational studies to exist in prokaryotes. This family is expected to be involved in the specialized form of genomic DNA repair through the non-homologous end joining pathway which acts to join double-stranded breaks (DSBs) or to promote genetic diversity under conditions of selection pressures. Accordingly, the putative LigATII was amplified from the whole genome DNA amplification of LCL. Sanger sequencing confirmed the sequence of the gene before cloning into pET100 Topo directional expression vector. The cloned LigATII was transformed into a temperature sensitive mutant strain of Escherichia coli; strain GR501, with mutation in the DNA ligase gene. LigATII complemented the temperature sensitive strain at the non-permissive temperature (43◦C) verifying the in vivo functional activity. The biochemical characteristics of the novel LigATII protein will be described.